MENINGKATAN KREATIFITAS PESERTA DIDIK DALAM MENULIS KARTU UCAPAN BERBAHASA INGGRIS MELALUI METODE PRAKTIK - Suwanto Suwanto (LPMP Provinsi DKI Jakarta, 2022)
The ability to write greeting cards is still low, influenced by lack of vocabulary mastery, difficulty in composing good and correct sentences. The objectives (1) are to explain the process of the practical method, (2) to explain the results of the practical method, (3) to explain the changes in students' behavior. The research method is classroom action research. The subjects are VIIIF SMPN 17 Pontianak. Data collection used observation sheets and tests. Data analysis; normality, homogeneity and one sample test. Research result; first, the process to increase creativity includes 6 steps; (a) determining basic questions, (b) designing project plans, (c) preparing schedules, (d) Monitoring students and project progress, (e) Testing results, (f) Evaluating experiences. Second, the results of the calculation of p (0.200) are greater than 0.05 (α 0.05), normally, the significance of p (0.209) is obtained >, homogeneous, there are differences in the initial ability and the end after students take part in the practical method of sig. (0.030) < = 0.05. Third, the change in behavior was originally quite active (45%) to be active (68.18%). The average creative dimension that is integrated in the project of making greeting cards in the aspect of content is 3.27, design 3.09, picture 2.91 and objective 2.82. Students can make the correct greeting cards according to the contents of the greeting cards, students can design greeting cards, create images that match the greeting cards, and have formulated the objectives of the greeting cards correctly.